Building and Developing Student Entrepreneurial Intentions Through Self-Efficacy and Entrepreneurship Education in Higher Education - Ferdinand Salomo Leuwol; Bambang Irawan; Yohannes Don Bosco Doho; Tribowo Rachmat Fauzan; Budi Mardikawati (Universitas Muhammadiyah Enrekang, 2023)
This research is motivated by the importance of building and developing entrepreneurial intentions for students. The purpose of this study is to examine and analyze the effect of self-efficacy and entrepreneurship education on entrepreneurial intentions. This research uses a quantitative approach with a survey method. The sampling technique used purposive sampling of 100 students. The instruments used were observation, questionnaires and documentation. The data analysis technique used is the classical assumption, correlation analysis, and multiple linear regression analysis including hypothesis testing T test, F test and R 2 test. The results of this study indicate: 1) Self-efficacy has a positive and significant effect on entrepreneurial intentions, 2) Entrepreneurship education has a positive and significant effect on entrepreneurial intentions, and 3) Self-efficacy and entrepreneurship education has a positive and significant effect on entrepreneurial intentions. The conclusion of this research is that if universities want to build and develop students' entrepreneurial spirit, then universities need to improve student self-efficacy and entrepreneurship education.